What are The Causes of Exclusive Breastfeeding Failure? : A Systematic Review - Arifarahmi Arifarahmi; Asrial Asrial; M Rusdi Rusdi; Solha Elrifda (Syntax Corporation Indonesia, 2023)
Exclusive breastfeeding has tremendous health benefits for infants, including boosting the immune system, reducing the risk of disease, and supporting optimal growth and development. Although the importance of exclusive breastfeeding is widely recognized, there are still failures in exclusive breastfeeding practices in many countries, including the factors that cause them. This study aims to analyze the factors that lead to exclusive breastfeeding failure. This study used a systematic literature review method. The data collection technique in this study was carried out by searching literature in the Google Scholar and Scopus databases. Data analysis was carried out using qualitative methods. The results showed that the factors inhibiting exclusive breastfeeding were infant mother's knowledge, family support including mother, mother-in-law, and husband, mother's employment status, breast care, breastfeeding coupled with formula and complementary foods, and milk production during breastfeeding